PENGELOLAAN KAS TERHADAP LIKUIDITAS PERUSAHAAN CV. SULAM JAYA FURNITURE KOTA SAMARINDA - Ida Rahmawati3, Debora Septiarani1, Titin Ruliana2 (EKONOMIA, 2021)
This research aims to know and analysis optimal of cash management and liquidity conducted by CV. Sulam Jaya Furniture. The grand theory of this research is financial management. This type of research uses quantitative descriptive with case study method. The analysis too is that used are cash management analysis by determining the optimal cash balance of the company and analysis of company liquidity ratios whitch are current ratio, cash ratio, and quick ratio.The results of the study and analysis can be concluded that cash management of CV. Sulam Jaya Furniture is optimal cash balance that must be provided by company. Meanwhile, seen from the company’s liquidity, cash management conducted by CV. Sulam Jaya Furniture can guarantee its company liquidity. this is because average liquidity ratio of the company overall can fulfill the standard that applied.Expected that CV. Sulam Jaya Furniture can manage thei cash well. So, the company’s liquidity also remains in good condition. The company must maintain good relations with financial institutions and other parties who can help smoothness of the company.